Not So Strange Bedfellows The Nexus of Politics and Religion in the 21st Century. - Imre, Rob.; Jose, Jim. (Newcastle upon Tyne : Cambridge Scholars Publishing, 2013)
At the intersection of politics and religion is a nexus of belief in doctrine and adherence to socio-political cultural conventions. Lines of communication and methods of belonging permeate both spheres, enabling their respective participants, especially the (often self-described) 'true believers', to bond and belong, and most importantly to adhere to their various belief systems. Traditionally, this nexus has been approached from a standpoint that posits the idea of secularity as the governi...
Table of contents; list of tables and figures; part i; chapter one; part ii; chapter two; chapter three; chapter four; chapter five; part iii; chapter six; chapter seven; chapter eight; chapter nine; chapter ten; chapter eleven; chapter twelve; part iv; chapter thirteen; chapter fourteen; contributors; index
Description based upon print version of record.
Keywords: Political development; Religion -- 21st century; Religion and politics; Religion and politics; Political development; POLITICAL SCIENCE / Political Process / Political Advocacy; Electronic books